Conductive paste used between consumable electrode and clamping device and preparation and application methods thereof
By mixing conductive paste with copper-based conductive powder and other components, the problem of unstable conductivity between the consumable electrode and the clamping device is solved, and efficient conductivity and stable electroslag remelting process is achieved, which significantly improves the uniformity of product quality.
Patent Information
- Application Number
- CN202411920974.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the conductivity between the consumable electrode and the clamping device is unstable, resulting in current fluctuations and uneven temperatures, which affects the stability of the electroslag remelting process and product quality.
A conductive paste consisting of copper-based conductive powder, conductive adhesive, lubricant, antioxidant, dispersant, nano-silicon carbide and rare earth elements is used to form a conductive paste with high conductivity and wear resistance by mixing the proportion and particle size of these components, and ensure its stability in a high temperature environment through a specific stirring and heating process.
It significantly improves the conductivity and stability of the conductive paste, reduces contact resistance, saves electricity, and improves the stability of the electroslag remelting process and the uniformity of product quality.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electroslag remelting, and in particular relates to a conductive paste used between a consumable electrode and a clamping device and a preparation and application method thereof. Background Art
[0002] As an important metal refining and forming method, the electroslag remelting process is widely used in modern industry. During the electroslag remelting process, the current flows through the slag pool through the consumable electrode to generate resistance heat, which melts the metal into a liquid state, thereby achieving purification and solidification. However, the conductivity between the consumable electrode and the clamping device has a crucial impact on the efficiency, energy consumption and product quality of the entire process.
[0003] At present, the common conductive connection methods between consumable electrodes and clamping devices mainly include direct contact, the use of simple conductive media, etc. However, these methods have many shortcomings. For example, patent application number: CN202320598051.3 discloses an electrode clamping device for electroslag remelting, including a mounting seat connected to the end of the consumable electrode, and a plurality of locking units installed on the side of the fixed seat. The method of direct contact, but due to factors such as surface roughness, oxide layer, and microscopic unevenness, the actual contact area is small, resulting in a large contact resistance. This will not only increase the loss of electric energy, but may also cause local overheating, affect the uniformity of current distribution, and thus have an adverse effect on the quality of the remelted metal.
[0004] In addition, in actual production, simple conductive media, such as traditional conductive grease or graphite powder, are used. Although the conductivity is improved to a certain extent, there are often problems such as unstable conductivity, volatility, and poor temperature resistance. During the high temperature and long-term electroslag remelting process, these conductive media are prone to failure, resulting in increased contact resistance, which affects the stability of the process and the consistency of the product. In the production of some high-end special steels, the temperature control accuracy and composition uniformity during the remelting process are extremely high, and the current fluctuations and temperature unevenness caused by poor conductivity will seriously affect the performance and quality of the product. Summary of the invention
[0005] The purpose of the present invention is to provide a conductive paste used between a consumable electrode and a clamping device and a preparation and application method thereof, so as to enhance the temperature resistance of the conductive paste, meet the high temperature working environment requirements of the consumable electrode, and improve the stability of the conductive performance.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions:
[0007] A conductive paste used between a consumable electrode and a clamping device, comprising the following raw materials by weight percentage:
[0008] Copper-based conductive powder 50% to 60%;
[0009] Conductive adhesive 18% to 25%;
[0010] Lubricant 9% to 12%;
[0011] Antioxidants 4% to 8%;
[0012] Dispersant 3% to 8%;
[0013] Nano silicon carbide 1% to 4%;
[0014] Rare earth 1%~3%.
[0015] The copper-based conductive powder is pure copper powder with a particle size of 10 to 50 microns.
[0016] The conductive adhesive is an epoxy resin adhesive;
[0017] The lubricant is graphite with a particle size of 10 to 50 microns.
[0018] The antioxidant is benzotriazole; the dispersant is polyethylene glycol; and the rare earth is one or both of cerium oxide and lanthanum.
[0019] The particle size of the nano silicon carbide is 80 to 130 nanometers.
[0020] A method for preparing a conductive paste between a consumable electrode and a clamping device, comprising the following steps:
[0021] 1) Adding conductive adhesive into a stirring container, stirring and heating;
[0022] 2) When the temperature of the conductive adhesive is 75-85°C, slowly add copper-based conductive powder, nano silicon carbide, and rare earth in sequence, stirring for 5-10 minutes after each raw material is added; then add lubricant and dispersant, continue stirring for 2-5 minutes, and finally add antioxidant and stir evenly;
[0023] 3) Maintain the temperature of the stirring container at 80±2°C and continue stirring for 2 to 3 hours;
[0024] 4) Stop heating and continue stirring until the stirring container cools naturally to room temperature.
[0025] The stirring speed in step 1) to step 3) is 500 to 800 rpm.
[0026] The stirring speed in step 4) is 100 to 200 rpm.
[0027] A method for applying a conductive paste between a consumable electrode and a clamping device, comprising the following steps:
[0028] 1) Before electroslag remelting, clean the contact surface between the consumable electrode and the clamping device to remove oil, dust and oxide layer on the surface;
[0029] 2) Apply the conductive paste to the contact surface of the consumable electrode and the contact surface of the clamping device, with a total thickness of 0.5 to 1 cm.
[0030] Functions of the components in the conductive paste used between the consumable electrode and the clamping device:
[0031] 1. Copper-based conductive powder
[0032] Conductive function: High-purity copper powder has excellent conductivity and is the key to the conductive paste to achieve the conductive function. The particle size of high-purity copper powder can ensure that there is enough surface area to fully contact with other components to form a good conductive network, but it is not too fine to easily agglomerate or too coarse to affect the uniformity of the conductive paste. Therefore, its particle size is controlled at 10 to 50 microns.
[0033] Heat conduction effect: Copper has good heat conduction properties. During the conduction process, it can quickly conduct away the heat generated locally to avoid affecting the conductivity or damaging the connection parts due to heat accumulation.
[0034] Mechanical support: Copper powder particles play a certain mechanical support role in the conductive paste, which helps to maintain the structural stability of the conductive paste. When the conductive paste is squeezed or stretched by external force, the copper powder particles can bear part of the stress.
[0035] Cooperation with adhesives: Combined with conductive adhesives to form a stable structure to ensure that the conductive performance is not affected under high temperature conditions.
[0036] 2. Conductive adhesive
[0037] Bonding and fixing effect: Epoxy resin adhesive with excellent conductivity and bonding strength can firmly bond copper powder particles together to ensure the stability of the conductive path. At the same time, it can also closely connect the conductive paste to the consumable electrode and the surface of the clamping device to prevent the conductive paste from falling off or shifting during use. Conductive adhesive can isolate oxygen and moisture to a certain extent, and protect copper powder from oxidation together with antioxidants. The sealing layer formed by the conductive adhesive can reduce the contact opportunity between the oxidant and the copper powder, thereby enhancing the effect of the antioxidant. At the same time, the antioxidant can also protect the conductive adhesive from the effects of oxidation and extend its service life. For example, when the clamping device is lowered, the conductive adhesive can ensure that the conductive paste always maintains good contact with the connection part.
[0038] Filling gaps: Conductive adhesive can fill the gaps between copper powder particles, making the structure of the conductive paste denser and reducing the impact of air gaps on the conductive properties. In addition, it can also fill the microscopic unevenness on the surface of the electrode and the clamping device to increase the contact area and conductive properties.
[0039] Insulation protection: To a certain extent, conductive adhesive can also play an insulating protection role. It can prevent copper powder particles from direct contact with the external environment and reduce the impact of oxidation, corrosion and other factors on the conductive properties. At the same time, it can also prevent the occurrence of electrical faults such as leakage and short circuit.
[0040] 3. Antioxidants
[0041] Preventing copper powder from oxidizing: The antioxidant benzotriazole molecules contain polar groups such as nitrogen atoms, which can chemically adsorb to copper atoms on the surface of copper powder. At the molecular level, benzotriazole molecules form coordination bonds with copper atoms through the lone pair of electrons in their nitrogen atoms, thereby forming a stable protective film on the surface of copper powder. This protective film prevents oxidants such as oxygen and moisture in the air from directly contacting copper powder, preventing copper atoms from being oxidized into substances with poor conductivity such as copper oxide. At the same time, the adsorption of antioxidant molecules will not hinder the conduction of electrons in copper powder, ensuring the stability of conductive properties.
[0042] Stabilizing the conductivity: Antioxidants can also stabilize the conductivity of conductive paste. Even in an oxidizing environment, due to the protection of antioxidants, the conductivity of copper powder changes little, thus ensuring the stable transmission of current.
[0043] 4. Dispersant
[0044] Uniform dispersion: Polyethylene glycol is used as a dispersant. Polyethylene glycol molecules interact with each component through their polar groups. Polyethylene glycol molecules can be adsorbed on the surface of copper powder particles, and prevent the agglomeration of copper powder particles through steric hindrance and electrostatic repulsion. This allows the copper powder particles to be evenly dispersed in the conductive paste, increasing the contact opportunities between copper powder particles and improving the conductive properties. It can also entangle with the epoxy resin molecules in the conductive adhesive or form weak interactions such as hydrogen bonds, promoting the uniform distribution of the conductive adhesive between the copper powder particles and improving the bonding effect of the conductive adhesive.
[0045] Improving stability: Dispersants can improve the stability of conductive pastes and prevent the components from settling, agglomerating or separating. During storage and use, evenly dispersed conductive pastes can maintain good performance and are not prone to stratification or agglomeration.
[0046] Promote mixing: In the process of preparing conductive paste, dispersants help to fully mix the ingredients. It can reduce the interfacial tension between the ingredients, making them easier to blend with each other and form a uniform mixture.
[0047] 5. Nano-silicon carbide
[0048] Enhance wear resistance: Nano silicon carbide has extremely high hardness and wear resistance, and adding it to the conductive paste can significantly improve its wear resistance. In the relative movement between the electrode and the clamping device, nano silicon carbide can withstand greater friction and reduce the wear of the conductive paste.
[0049] Improve thermal stability: Nano silicon carbide has good thermal stability and can maintain structural stability in high temperature environments. It can withstand high temperatures without significant performance changes, thereby improving the thermal stability of the conductive paste. In high-temperature electroslag furnace equipment, nano silicon carbide can ensure that the conductive paste can still maintain good conductivity and mechanical strength at high temperatures.
[0050] Improvement of electrical conductivity: Nano-SiC particles can form local contact points with copper powder particles, increasing the complexity of the conductive path. At the same time, the high hardness of nano-SiC can protect the copper powder particles from wear and tear, maintaining electrical conductivity.
[0051] 6. Rare Earth
[0052] Improve high temperature stability: Rare earth elements have high thermal stability and can maintain the stability of their chemical properties at high temperatures. Adding rare earth element additives can improve the stability of conductive paste in high temperature environments and prevent the decline of conductive properties. For example, during high temperature heat treatment, rare earth element additives can protect the conductive paste from the influence of high temperature and maintain good conductive properties. Rare earth ions can be adsorbed at the grain boundaries or defect positions of copper powder particles, and refine the grains and improve the conductive properties by affecting the crystal structure and electronic band structure of copper powder. The presence of rare earth ions can also change the chemical activity of the copper powder surface, enhance the adsorption effect of antioxidants, and improve the high temperature stability of the conductive paste.
[0053] At the same time, rare earth element additives can also interact with conductive adhesives, lubricants and other ingredients to optimize the comprehensive performance of conductive pastes. For example, rare earth ions can form coordination bonds with epoxy resin molecules in conductive adhesives to enhance bonding strength; they can also work synergistically with lubricants to improve lubrication performance.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] 1. The conductive paste used between the consumable electrode and the clamping device of the present invention has been significantly improved in performance. Through the formulated combination of ingredients, its conductivity is greatly improved compared with the traditional conductive method, which means that in the electroslag remelting process, the current can pass through the contact part between the consumable electrode and the clamping device more smoothly, thereby significantly reducing the contact resistance. The reduction in contact resistance directly leads to a significant reduction in power consumption, and the energy-saving effect is extremely significant. According to actual application data, under the same production conditions, power consumption is reduced by about 25%. This not only saves a lot of energy costs for enterprises, but also helps to reduce the pressure of energy consumption on the environment.
[0056] 2. The addition of nano-silicon carbide enhances the wear resistance of the conductive paste, allowing it to maintain good physical properties during long-term use, especially when the consumable electrode and the clamping device are in frequent contact and friction, reducing the decline in conductivity caused by wear. At the same time, nano-silicon carbide also improves the thermal stability of the conductive paste, allowing it to work stably in the high-temperature environment of electroslag remelting and is not prone to performance degradation.
[0057] 3. The introduction of rare earth elements plays a unique role. They can refine the grains and optimize the microstructure of the conductive paste, thereby further improving the conductive performance. In a high temperature environment, rare earth element additives help maintain the stability of the conductive paste, reduce structural changes caused by factors such as thermal expansion and contraction, and ensure long-term stable conductive effects. In addition, rare earth elements can also improve the interface bonding state between the consumable electrode and the clamping device, and improve the reliability of the conductive connection.
[0058] 4. Due to the comprehensive optimization of the performance of the conductive paste, the stability of the conductive connection has been greatly enhanced. During the remelting process, the current distribution is more uniform, which effectively reduces the current fluctuation and temperature unevenness caused by poor contact. This makes the temperature distribution during the remelting process more uniform and consistent, avoiding local overheating or overcooling. The improvement of temperature uniformity is of vital importance to the quality uniformity of the remelted product, significantly reducing the defects and component segregation inside the product, and improving the consistency of the mechanical and chemical properties of the product. DETAILED DESCRIPTION
[0059] The present invention is described in detail below, but it should be noted that the implementation of the present invention is not limited to the following embodiments.
[0060] A method for preparing a conductive paste between a consumable electrode and a clamping device, comprising the following steps:
[0061] 1) Prepare a clean, dry, high temperature resistant mixing container without impurities. Use a suitable cleaning agent to clean it thoroughly, and then blow it dry with dry compressed air or hot air.
[0062] 2) Add conductive adhesive to the stirring container, stir and heat; when the temperature of the conductive adhesive is 80°C, slowly add 55% copper-based conductive powder (particle size controlled at 10-50 microns), 3% nano-silicon carbide, and 2% rare earth in sequence, stirring for 5-10 minutes after adding each raw material; then add 10% lubricant and 5% dispersant, continue stirring for 2-5 minutes, and finally add antioxidant and stir evenly; during the addition process, ensure that each component is evenly dispersed to avoid local agglomeration or uneven concentration. Keep stirring at 80°C for 2 hours during the stirring process. The stirring speed should be moderate to ensure that the components are fully mixed without excessive bubbles or splashing. During this process, physical and chemical reactions occur between the components, the adhesive gradually melts and fully wraps the copper powder particles, and the lubricant, antioxidant, dispersant, nano-silicon carbide and rare earth element additives are evenly distributed in the system to form a uniform and stable mixture.
[0063] 3) After stirring for 2 hours, stop heating and allow the mixture to cool naturally to room temperature while stirring. As the temperature decreases, the adhesive gradually solidifies, eventually forming a new copper-based conductive paste with a certain viscosity and good conductive properties.
[0064] The use of high temperature resistant copper-based conductive powder and conductive adhesive ensures that it does not melt or soften at high temperatures, maintaining a stable structure; in terms of microstructure, the softening flow of the conductive adhesive makes the conductive particles contact more closely, and the addition of nano silicon carbide and rare earth elements strengthens the structure and increases the complexity of the conductive path; antioxidants form a protective film on the surface of the conductive particles to prevent oxidation and corrosion, while the overall structure of the conductive paste plays a sealing and isolation role to reduce the impact of the external environment. These factors work together to enable the conductive paste to achieve normal conductivity in a high temperature environment.
[0065] Application method of conductive paste:
[0066] 1) Before the electroslag remelting process, the contact surface between the consumable electrode and the clamping device should be strictly cleaned. Use organic solvents or special cleaning agents to remove impurities such as oil, dust and oxide layer on the surface to ensure that the surface is clean, dry and free of any contaminants.
[0067] 2) After cleaning, use a coating tool (such as a scraper, brush or spray gun, etc.) to evenly apply the prepared conductive paste on the contact surface between the consumable electrode and the clamping device. The coating thickness is controlled to 0.5 to 1 cm to ensure a good conductive effect while avoiding excessive material waste.
[0068] During the application process, ensure that the conductive paste completely covers the contact surface without any missing or uneven areas. After the application is completed, carefully check the application quality and reapply or trim if necessary.
[0069] Finally, the consumable electrode coated with conductive paste is assembled with the clamping device, and the remelting operation is carried out according to the normal electroslag remelting process parameters and operation procedures. During the entire use process, care should be taken to prevent the conductive paste from being contaminated by the outside world or mechanically damaged to ensure its stable and reliable performance.
[0070] Example 1
[0071] The composition of the conductive paste used between the consumable electrode and the clamping device:
[0072] 50% copper-based conductive powder (particle size 10-40 microns), 25% conductive adhesive, 10% lubricant (graphite), 5% antioxidant (benzotriazole), 5% dispersant (polyethylene glycol), 3% nano-silicon carbide, and 2% rare earth element additive (lanthanum).
[0073] Preparation process:
[0074] Add conductive adhesive to the stirring container, stir and heat (speed is 600 rpm); when the temperature of the conductive adhesive is 75°C, slowly add copper-based conductive powder, nano silicon carbide, and rare earth in turn, stirring for 5 to 10 minutes after each raw material is added; then add lubricant and dispersant, continue stirring for 2 to 5 minutes, and finally add antioxidant and stir evenly; during the addition process, ensure that each component is evenly dispersed to avoid local agglomeration or uneven concentration. Keep stirring at 78°C for 2.5 hours during the stirring process. Then cool naturally to room temperature while continuing to stir (150 rpm).
[0075] The prepared conductive paste is evenly applied to the connection between the consumable electrode and the clamping device, with a thickness of 0.7±0.05 cm and a width slightly wider than the clamping device.
[0076] Application effect: In the electroslag remelting process, the power consumption is reduced by about 22% and the quality uniformity of the steel ingot is good.
[0077] Embodiment 2:
[0078] The composition of the conductive paste used between the consumable electrode and the clamping device:
[0079] Copper-based conductive powder 60% (particle size 20-50 microns), conductive adhesive 18%, lubricant 12% (graphite), antioxidant 5% (benzotriazole), dispersant 3% (polyethylene glycol), nano-silicon carbide 1%, rare earth element additive (cerium oxide) 1%.
[0080] Preparation process:
[0081] Add conductive adhesive to the stirring container, stir and heat (speed is 650 rpm); when the temperature of the conductive adhesive is 85°C, slowly add copper-based conductive powder, nano silicon carbide, and rare earth in turn, stirring for 5 to 10 minutes after each raw material is added; then add lubricant and dispersant, continue stirring for 2 to 5 minutes, and finally add antioxidant and stir evenly; during the addition process, ensure that each component is evenly dispersed to avoid local agglomeration or uneven concentration. Keep stirring at 80°C for 1.5 hours during the stirring process. Then cool naturally to room temperature during continuous stirring (120 rpm).
[0082] The prepared conductive paste is evenly applied to the connection between the consumable electrode and the clamping device, with a thickness of 0.8±0.05 cm and a width slightly wider than the clamping device.
[0083] Application effect: Power consumption is reduced by about 20%, and the chemical composition deviation of the steel ingot is smaller.
[0084] Embodiment 3:
[0085] The composition of the conductive paste used between the consumable electrode and the clamping device:
[0086] 58% copper-based conductive powder (particle size 15-45 microns), 22% conductive adhesive, 10% lubricant (graphite), 4% antioxidant (benzotriazole), 4% dispersant (polyethylene glycol), 1.5% nano-silicon carbide, rare earth element additives (0.5% each of lanthanum and cerium oxide).
[0087] Preparation process:
[0088] Add conductive adhesive to the stirring container, stir and heat (speed is 700 rpm); when the temperature of the conductive adhesive is 82°C, slowly add copper-based conductive powder, nano silicon carbide, and rare earth in turn, stirring for 5 to 10 minutes after each raw material is added; then add lubricant and dispersant, continue stirring for 2 to 5 minutes, and finally add antioxidant and stir evenly; during the addition process, ensure that each component is evenly dispersed to avoid local agglomeration or uneven concentration. Keep stirring at 80°C for 2 hours during the stirring process. Then cool naturally to room temperature during continuous stirring (120 rpm).
[0089] The prepared conductive paste is evenly applied to the connection between the consumable electrode and the clamping device, with a thickness of 1±0.05 cm and a width slightly wider than the clamping device.
[0090] Application effect: Power consumption is reduced by about 24%, and the performance of the remelted products is stable.
[0091] Principle: After the power source is drawn out, it reaches the clamping device through transmission lines such as conductive cables. When the current reaches the clamping device, it is first distributed in the conductive part of the clamping device, and then reaches the conductive paste. The current first flows from the clamping device into the conductive adhesive of the conductive paste. Although the conductive adhesive itself is not as conductive as metal, it can form a conductive network in the presence of conductive particles.
[0092] During smelting, the slag pool temperature is around 1700℃, and the top temperature of the consumable electrode can reach 800℃. At this high temperature, the metal is prone to oxidation reaction, and the oxide layer on the surface of the consumable electrode will increase the contact resistance and reduce the conductivity. At this time, it is particularly important to improve the conductivity between the consumable electrode and the clamping device. The surface state of copper powder particles at high temperatures has an important influence on the conductivity. In the conductive paste system, antioxidants such as benzotriazole can react with the surface of copper powder particles to form a protective film to prevent further growth of the oxide layer and ensure that the transmission of electrons on the particle surface is not hindered. Dispersants such as polyethylene glycol can be adsorbed on the surface of copper powder particles, prevent particle agglomeration through steric hindrance effect, maintain the activity of the particle surface, and facilitate the transmission of electrons. Ingredients such as nano-silicon carbide and rare earth element additives may also interact with the surface of copper powder particles, change the surface electronic state, and further optimize the conductivity.
[0093] Conductive adhesives not only play the role of bonding copper powder particles in conductive pastes, but also participate in the conductive process. Conductive adhesives such as epoxy resins usually contain certain polar groups and conductive fillers. Polar groups can physically or chemically adsorb to the surface of copper powder particles, which not only enhances the bonding force, but also provides a bridge for the transmission of electrons.
[0094] The main function of graphite lubricant in conductive paste is to reduce the friction between the clamping device and the consumable electrode. At the microscopic level, the layered structure of graphite enables it to form a lubricating film on the friction surface, reducing the friction coefficient. It protects the conductive paste and the electrode surface and reduces damage to the conductive path. When the clamping device and the consumable electrode move relative to each other, the lubricant can prevent the copper powder particles and the conductive adhesive from being subjected to excessive shear forces, thereby maintaining the integrity of the conductive path. For example, during the insertion and removal of the electrode, the lubricant can reduce the wear on the conductive paste and extend its service life. Graphite lubricants have good thermal conductivity and can help conduct the generated electrical heat away from the contact area. This helps to reduce the temperature of the conductive paste and prevent the degradation of conductivity or other adverse effects due to excessive temperature.
[0095] Nano silicon carbide has high hardness and good thermal stability. One of its functions in conductive paste is to enhance the conductivity. Nano silicon carbide particles can form local contact points with copper powder particles, increasing the complexity of the conductive path. These contact points can provide additional electron transmission channels and improve the transmission efficiency of electrons. Rare earth element additives such as cerium oxide or lanthanum can refine the grains, change the crystal structure and electronic band structure of copper powder particles, and thus improve the conductivity. Rare earth element additives can also interact with the surface of copper powder particles, enhance the antioxidant capacity and thermal stability of copper powder, and further optimize the conductive properties.
Claims
1. A conductive paste used between a consumable electrode and a clamping device, characterized in that: It is composed of the following raw materials by weight percentage: Copper-based conductive powder 50% to 60%; Conductive adhesive 18% to 25%; Lubricant 9% to 12%; Antioxidants 4% to 8%; Dispersant 3% to 8%; Nano silicon carbide 1% to 4%; Rare earth 1%~3%.
2. The conductive paste used between the consumable electrode and the clamping device according to claim 1, characterized in that: The copper-based conductive powder is pure copper powder with a particle size of 10 to 50 microns.
3. The conductive paste used between the consumable electrode and the clamping device according to claim 1, characterized in that: The conductive adhesive is an epoxy resin adhesive.
4. The conductive paste used between a consumable electrode and a clamping device according to claim 1, characterized in that: The lubricant is graphite with a particle size of 10 to 50 microns.
5. The conductive paste used between the consumable electrode and the clamping device according to claim 1, characterized in that: The antioxidant is benzotriazole; the dispersant is polyethylene glycol; and the rare earth is one or both of cerium oxide and lanthanum.
6. The conductive paste used between a consumable electrode and a clamping device according to claim 1, characterized in that: The particle size of the nano silicon carbide is 80 to 130 nanometers.
7. A method for preparing a conductive paste used between a consumable electrode and a clamping device as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: 1) Adding conductive adhesive into a stirring container, stirring and heating; 2) When the temperature of the conductive adhesive is 75-85°C, slowly add copper-based conductive powder, nano silicon carbide, and rare earth in sequence, stirring for 5-10 minutes after each raw material is added; then add lubricant and dispersant, continue stirring for 2-5 minutes, and finally add antioxidant and stir evenly; 3) Maintain the temperature of the stirring container at 80±2°C and continue stirring for 2 to 3 hours; 4) Stop heating and continue stirring until the stirring container cools naturally to room temperature.
8. The method for preparing a conductive paste between a consumable electrode and a clamping device according to claim 7, characterized in that: The stirring speed in step 1) to step 3) is 500 to 800 rpm.
9. The method for preparing a conductive paste between a consumable electrode and a clamping device according to claim 7, characterized in that: The stirring speed in step 4) is 100 to 200 rpm.
10. A method for applying the conductive paste between a consumable electrode and a clamping device as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: 1) Before electroslag remelting, clean the contact surface between the consumable electrode and the clamping device to remove oil, dust and oxide layer on the surface; 2) Apply the conductive paste to the contact surface of the consumable electrode and the contact surface of the clamping device, with a total thickness of 0.5 to 1 cm.
Citation Information
Patent Citations
Electrode clamping device for electroslag remelting
CN219470147U